Decision support of facilities management practice in high rise buildings - Yahya, Mohamad Ridzuan; Ibrahim, Md. Najib (2011)
It is vital to prioritize on developing facilities management (FM) decision support in operation and maintenance of high rise buildings in order to make sure building performance and building condition are excellent all the time. In Malaysia, there are various obstacles that FM is facing in managing all maintenance activities in high rise building. The fundamental issue is to provide advance supporting technology of building systems in order to sustain sufficient economical and technical aspect in FM decision support. Ten high rise buildings were randomly selected in Klang Valley, Malaysia which interviewed building owners, FM personnel, building maintenance personnel, out sourced consultants/contractors, occupants and potential tenants based on the economical and technical aspects of design and maintenance which are the quality, safety and service in FM. It is evident from the findings that FM decision support practice in Malaysia is still lacking of human system aspect due to the knowledge and quality of building design and maintenance such as workmanship, response time, down time, request for repairs, building audit as well as operational benchmarks improvement were not implemented consistently. In addition, operation and maintenance more concentrated on corrective maintenance rather than preventive maintenance. However, in technology system aspect, most high rise buildings is able to utilize advance building technology such as building automation system (BAS) in order to provide a better service. The paper concludes that FM decision support practice in Malaysia is still far behind to reach an intelligent building system of FM standard known as a building equipped with advance and sophisticated technologies. In addition, it has not been adopted as rapidly and extensively as expected because of lack of information and knowledge support to the entire group of professionals involved at the design stage until future maintenance of a building. This paper provides a brief general suggestion on a system approach for the decision support of FM by adopting economical and technical aspects in order to structure the process involving various stakeholders. The Life Cycle Costing (LCC) analysis is a method used to assess design alternatives considering all the significant costs of ownership. The new technologies development of maintenance activities in FM should be given high priority.